PENGARUH MEDIA PAPAN KONVERSI BERAT TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS III DI MI MASJID AL-AKBAR SURABAYA - Tyssa Marietha Cahyani; Sulthon Mas'ud; Erwin Sarwanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning media plays an important role in supporting students' understanding, especially in abstract material such as the conversion of units of weight. Good media is media that can have a positive impact and influence on its users. Therefore, this study aims to determine how much influence the use of Weight Conversion Board learning media has on the learning outcomes of 3rd grade students of MI Masjid Al- Akbar Surabaya. This research uses a quantitative approach with descriptive methods. The research subjects amounted to 16 students, and the data was obtained through a post-test after learning took place for one month using the media. The results of the analysis show that most students have met the KKM criteria standard of 70. Concrete visualization and direct manipulation through the conversion board are proven to help students understand the concept of weight conversion more meaningfully. Even so, some students still need guidance in order to get the appropriate results. So it can be concluded that the use of media alone is not enough to require further strengthening to support learning for students.